RARE-32. POLYMORPHOUS LOW-GRADE NEUROEPITHELIAL TUMOR OF THE YOUNG (PLNTY): GENETIC ANALYSIS CONFIRMS FREQUENT MAPK PATHWAY ACTIVATION. (11th November 2019) - Ida, Cristiane; Johnson, Derek; Kollmeyer, Thomas; Kim, DongKun; Kaufmann, Timothy; Kipp, Benjamin; Jenkins, Robert; Giannini, Caterina
Abstract: Polymorphous low-grade neuroepithelial tumor of the young (PLNTY) is a recently described epileptogenic tumor characterized by oligodendroglioma-like components, aberrant CD34 expression, and genetic MAPK pathway activation through alterations such as BRAF V600E mutation, and FGFR2-KIAA1598/CTNNA3 and FGFR3-TACC3 fusions. We report the molecular profiling of PLNTY in 9 patients, 7 female: 2 male, median age at diagnosis of 16 years (range, 5–34). All tumors were supratentorial with diagnostic morphological features of PLNTY including oligodendroglioma-like areas and strong diffuse CD34 immunostaining. Four (of 9; 44%) tumors were positive for BRAF V600E immunostain, indicating the presence of a BRAF V600E mutation. The 6 cases evaluated for IDH status were negative by IDH1-R132H immunostain (n=5; 3 BRAF V600E-negative and 2 BRAF V600E-positive) or by NGS (n=1; BRAF V600E-negative). Oncoscan chromosomal microarray performed in 5 BRAF V600E-negative tumors showed recurrent copy number changes including gain of whole chromosomes 5, 7, 8, 9, 12, 18, 19, 20, 21 and X, and loss of chromosomes 1, 2, 10q, 13, 22 and Xq. The 10q losses (n=2) were highly suggestive of an FGFR2-KIAA1598 and of a potentially novel FGFR2 underlying fusion event in one case each. Custom targeted neuro-oncology DNA and RNA NGS panel performed in 2 cases revealed a fusion similar to fusions previously reported in pilocytic astrocytoma: one with a KIAA1549-BRAF (exon 15-exon 9) fusion associated with a 7q34 ~785 kilobase deletion rather than the characteristic ~2 megabase duplication seen in pilocytic astrocytoma, and another with a QKI-NTRK2 (exon 6-exon 15) fusion associated with a 9q21 ~191 kilobase duplication disrupting NTRK2 . The KIAA1549-BRAF fusion-positive case also had a TP53 mutation with loss of whole chromosome 17, suggesting TP53 complete inactivation. This study confirms that PLNTY is a low-grade neuroepithelial tumor with frequent MAPK pathway activation and expands the spectrum of MAPK activating alterations observed in PLNTY.